"Jewish" Politics or the Politics of "Jews"?: On Israeli Nation-Statehood. (1st October 2020) - Yadgar, Yaacov
Abstract : This essay seeks to explicate a tension that lies at the very root of our discourse on Israel as a Jewish state. I argue that the academic and political fields tend to confuse and conflate two different, often contradictory understandings or constructions of the very meaning of Jewish politics. Schematically labelling these as Jewish politics versus the politics of Jews (and derived from these, the outlook of Israel as a "Jewish state" versus the notion of it being solely a "state of Jews"), I argue that the conflicting political and ideological constructions are nourished by different readings of Jewish identity and authenticity, which were first developed in Europe by leading (self-identified secular) Zionist ideologues, and later shaped mainstream readings of Israeli politics. The essay outlines the basic contours of this conceptual distinction, traces its roots in Zionist ideology (as developed in Eastern and Central Europe), and concludes with a consideration of the playing out of the tension at hand in contemporary Israeli politics.